Cannabidivarin alleviates neuroinflammation by targeting TLR4 co-receptor MD2 and improves morphine-mediated analgesia - Wang, Xue; Lin, Cong; Wu, Siru; Zhang, Tianshu; Wang, Yibo; Jiang, Yanfang; Wang, Xiaohui (Frontiers in Immunology, 2022)
Toll-like receptor 4 (TLR4) is a pattern-recognition receptor (PRR) that regulates the activation of immune cells, which is a target for treating inflammation. In this study, Cannabidivarin (CBDV), an active component of Cannabis, was identified as an antagonist of TLR4. In vitro, intrinsic protein fluorescence titrations revealed that CBDV directly bound to TLR4 co-receptor myeloid differentiation protein 2 (MD2). Cellular thermal shift assay (CETSA) showed that CBDV binding decreased MD2 stability, which is consistent with in silico simulations that CBDV binding increased the flexibility of the internal loop of MD2. Moreover, CBDV was found to restrain LPS-induced activation of TLR4 signaling axes of NF-κB and MAPKs, therefore blocking LPS-induced pro-inflammatory factors NO, IL-1β, IL-6 and TNF-α. Hot plate test showed that CBDV potentiated morphine-induced antinociception. Furthermore, CBDV attenuated morphine analgesic tolerance as measured by the formalin test by specifically inhibiting chronic morphine-induced glial activation and pro-inflammatory factors expression in the nucleus accumbent. This study confirms that MD2 is a direct binding target of CBDV for the anti-neuroinflammatory effect and implies that CBDV has great translational potential in pain management.